Effect of Irrigation on Footprint of Grey Water and Water Use Efficiency of Paddy Fields - XIAO Jianfeng; WU Mengyang; TANG Shuhai; CAO Xinchun (Guan'gai paishui xuebao, 2023)
【Objective】 Improving irrigation water use efficiency is important in developing sustainable agriculture. Taking paddy field as an example, this paper investigates how to achieve this goal via irrigation optimization. 【Method】 The study is based on changes in water and fertilizers measured in 2017—2018 from fields under four different irrigation methods: frequent-shallow irrigation (FSI), wet-shallow irrigation (WSI), controlled irrigation (COI), rain-catching and controlled irrigation (RCI). For each irrigation, we calculate its impact on drainage, grey water footprint (GWF), and water use efficiency combined with grey water footprint (WF). 【Result】 Drainage from different treatment ranged from 387.6 to 593.7 mm, with RCI and COI draining the least and highest water, respectively. The annual average GWF of FSI, WSI, COI and RCI is 386.3, 420.6, 431.2 and 273.1 mm, respectively. The percentage of blue, green, and gray water in all treatments is in the range of 6.0%~24.0%, 31.8%~58.0%, 37.0%~54.0%, respectively, with the RCI giving the greatest green footprint and least blue print. 【Conclusion】 Comparing traditional method and the proposed WF framework reveals that it is crucial to considering both drainage and GWF in evaluating water use efficiency of the paddy fields. For the four irrigation methods we compare, RCI is most efficient for paddy fields in the region we studied.